Computational design and fabrication of highly customizable architectural space frames: Making a flat-cut Weaire-Phelan structure. (March 2021) - Liu, Jingyang; Lee, Yi-Chin; Cardoso Llach, Daniel
This paper documents a computational approach to the design, fabrication, and assembly of customizable space structures built entirely out of flat-cut interlocking elements without the need of nodes, fasteners, cement, or glue. Following a Research by Design (RbD) methodology, we establish a framework comprising geometric and parametric modeling, structural analysis, and digital fabrication stages to examine the following research question: how might the modularity of a construction kit be combined with the plasticity of parametric descriptions to facilitate the design and fabrication of flat-cut space structures? We find that an adaptive joint design that resolves local deformations at the node and element levels can facilitate the construction of flat-cut space structures by making modular components responsive to local geometric, material, and mechanical demands. The research centers on the design and construction of an architecture-scale installation based on the Weaire-Phelan structure—an aperiodic space-filling geometric structure that approximates the geometry of foam—entirely out of flat-cut interlocking elements. Documenting the process in technical detail, as well as some limitations, the paper contributes to recent efforts to develop digital materials suitable for architectural applications. In addition, it contributes to extend the formal and architectural possibilities of flat-cut space structure design by facilitating "bottom-up" design explorations in concert with the structure's tectonic resolution.